(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This article presents reflections on a symposium on eudaimonia and music learning, from the perspective of one of the organizers. The symposium had been planned as a traditional, in person event in the United States, but was held online in response to the Spring, 2020 COVID-19 pandemic. The video-conferencing format created a more democratized liminal space that served to dissolve hierarchies and broaden participation.